2006
DOI: 10.1080/03639040500519235
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pigeon Pea and Plantain Starches on the Compressional, Mechanical, and Disintegration Properties of Paracetamol Tablets

Abstract: A study has been made of the effects of pigeon pea starch obtained from the plant Cajanus cajan (L) Millisp. (family Fabaceae) and plantain starch obtained from the unripe fruit of Musa paradisiaca L. (family Musaceae) on the compressional, mechanical, and disintegration properties of paracetamol tablets in comparison with official corn starch BP. Analysis of compressional properties was done by using density measurements, and the Heckel and Kawakita equations, whereas the mechanical properties of the tablets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The binding properties of pigeon pea starch paste have been evaluated in paracetamol tablet formulations [124]. The authors showed that the tensile strength of the tablets increased with increase in concentration of the starch while the Bt fracture index and disintegration time decreased.…”
Section: Pigeon Peamentioning
confidence: 99%
See 1 more Smart Citation
“…The binding properties of pigeon pea starch paste have been evaluated in paracetamol tablet formulations [124]. The authors showed that the tensile strength of the tablets increased with increase in concentration of the starch while the Bt fracture index and disintegration time decreased.…”
Section: Pigeon Peamentioning
confidence: 99%
“…Pigeon pea starch was found to be useful in producing strong tablets with minimal lamination and capping tendencies. The study concluded that pigeon pea starch could be more useful as binding agent when high speed tableting machine with short dwell time are used in the production of pharmaceutical tablets [124].…”
Section: Pigeon Peamentioning
confidence: 99%
“…It is also used as coating and dusting media for various types of tablet coating, such as sugar and enteric coating . Tropical starches have been investigated as binders, disintegrants, and glidants/lubricants in tablet formulations.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, cofused excipients offered significantly lower (p<0.05) values of P y . Lower values of P y implies faster onset of plastic deformation and the cofused excipients in this case would deform more readily under pressure on a high-speed tablet machine 33 , compared to the cogrinded types. Avicel (0 % DAM) showed the least P y and this is not surprising since it's a direct-compresion excipient.…”
Section: Figurementioning
confidence: 99%
“…The phase of particle rearrangement in the early stages of tablet compression is called the relative density at low pressure, D b and indicates the degree of fragmentation of particles 33 . Akin-Ajani et al 32 ., has reported that fragmentation of particles can occur concurrently with plastic and elastic deformation during compression.…”
Section: Figurementioning
confidence: 99%